Motor Ability of Elementary School Students in Upper Class - Sasmarianto, Sasmarianto; Kamarudin, Kamarudin (Champions: Education Journal of Sport, Health, and Recreation, 2023)
The problem in this research is that the motor skills of upper grade students at SDN 190 Pekanbaru are not yet known. The aim of this research was to determine the motor skills of upper class students at SDN 190 Pekanbaru. This research is descriptive research, with data collection methods using test techniques. The subjects used in this research were 41 upper class students at SDN 190 Pekanbaru. The test used was a motor ability test. The data analysis technique uses quantitative descriptive techniques. The results of the research show that the motor skills of students at SDN 190 Pekanbaru. There were 6 students (14.63%) who had good motor skills, 30 students (73.17%), and 5 students (12.20%) who had good motor skills. So it can be concluded that the upper class students of SDN 190 Pekanbaru, have motor skills mostly in the medium category with a total of 30 students (73.17℅).